PERSEPSI MASYARAKAT TERHADAP PENDIDIKAN DAN EKONOMI DI MASA PANDEMI COVID-19 - Dewi Rahmi Fauziah (e-Jurnal Aksioma Al-Musaqoh : Journal of Islamic Economics and Business Studies, 2022)
Knowledge is an alternative path that is needed by many people, because without knowledge, life is like darkness. Likewise with the economy, education without a strong economy also cannot run well, because the economy is very supportive of education. With the current condition of the world which is experiencing the Global Pandemic Corona Virus Disease-19 (Covid-19) as stated by the World Health Organization (WHO) on March 11, 2020.            The method used is descriptive qualitative method, where the data obtained in the field will be analyzed by revealing trends in thoughts and opinions to obtain more in-depth data from a literature review as well as by conducting interviews.            The results of this study show that the Covid-19 disruption has indirectly changed the mindset of the education and economic community. This pandemic has completely disrupted the education system. Schools that initially focused on traditional academic skills suddenly have to move to online learning which is more inclined to provide opportunities for critical thinking skills and adaptability. To encourage economic growth to continue in the midst of the economic crisis due to the COVID-19 outbreak, the Indonesian government has issued a stimulus which is summarized in 3 stimuli, namely fiscal stimulus, non-fiscal and the economic sector.Keyword : Pendidikan, Ekonomi dan Covid-19